2020
DOI: 10.1109/access.2020.3012633
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Grey Wolf Optimizer for Transformer Fault Diagnosis Using Dissolved Gases Considering Uncertainty in Measurements

Abstract: The transformer fault diagnosis based on dissolved gas analysis is greatly affected by the uncertainties existing in measured data during oil sampling, handling and storage. This work aims to develop an efficient code matrix based on dissolved gas percentages for accurate fault diagnosis considering measurement uncertainties. Fuzzy system is utilized to produce the rules that map the limits of gas ratios for different fault types. Each gas percentage range is divided into three regions represented by three fuz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 43 publications
(48 reference statements)
0
31
0
Order By: Relevance
“…The local best positions of individuals ( ) and global best position of the swarm ( ) are used to adjust the location of individuals using velocity ( +1 ) depending on space between locations of individuals and best positions of the gray wolf as in (27) to (29). The fittest modified positions are saved for the use in the upcoming GA loop [45].…”
Section: Hybrid Grey Wolf Optimizer (Gwo)mentioning
confidence: 99%
“…The local best positions of individuals ( ) and global best position of the swarm ( ) are used to adjust the location of individuals using velocity ( +1 ) depending on space between locations of individuals and best positions of the gray wolf as in (27) to (29). The fittest modified positions are saved for the use in the upcoming GA loop [45].…”
Section: Hybrid Grey Wolf Optimizer (Gwo)mentioning
confidence: 99%
“…More recently, the artificial neural network (ANN) is considered the most extensively used method in the literature for not only DGA but also diverse practical applications [ 15 , 16 , 17 ]. In [ 18 ], a fuzzy logic system is combined with a metaheuristic approach that is the hybrid grey wolf optimizer which adjusts DGA considering a diagnostic way that is robust against uncertainties. It is demonstrated that fuzzy logic, metaheuristics, and ANN can provide improved performance in general engineering applications [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The kernel principal component analysis (KPCA) is utilized to extract the features decreasing the model training time. A fuzzy system produced the rules to limit the gas ratio for transformer fault types considering three memberships for three regions of each gas percentage range [33]. The membership limits can be optimized using GWO, which developed the diagnostic code matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, combining the DGA methods and artificial intelligence methods to enhance the diagnostic accuracy of traditional DGA techniques requires much work, and diagnostic accuracy is still low. Therefore, the researchers attempted to use the optimization techniques to optimize the DGA method parameters or to optimize the classification parameters for the classification techniques [1], [21], [22], [28]- [33]. The optimization techniques maximize the agreement of predicting and the actual faults to develop the highest diagnostic accuracy of the transformer faults.…”
Section: Introductionmentioning
confidence: 99%